E-Commerce Kedai HP Berbasis Model View Controller (MVC) dengan Metode Scrum - Nadhif Azharandi; Septi Andryana; Aris Gunaryati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Kedai HP is a private distributor E-Commerce website that focuses on selling smartphones with various brands and prices. With the E-Commerce Kedai HP, people's purchasing power is increasing because they don't need to come directly to the shop to make transactions. The purpose of this research is to create an online distributor website to make it easier for people to transact and provide practicality in shopping. This study uses a Model View Controller (MVC) based system using the Scrum method, which is a method that is suitable for implementation in system development because it is flexible compared to the static waterfall method. The Model View Controller (MVC) is one of the design patterns that is currently widely used by some frameworks to develop applications so that the HP Store E-Commerce can run the transaction and reporting system automatically. Testing of this research uses the Blackbox Testing method which is a software testing technique that focuses on the functional specifications of a software. The test results show that the functional system that has been developed is functioning as it should.